2013
DOI: 10.1108/ijge-09-2012-0049
|View full text |Cite
|
Sign up to set email alerts
|

Creativity and implementations of new ideas

Abstract: Purpose – This paper uses a combination of organisation theory, gender theory and the work environment to study the generation and implementation of new ideas in organisations. How do employees' perceptions of organisational structure and the work environment affect idea generation and implementation, and how does gender moderate this relationship? Design/methodology/approach – The study develops and tests a structural equation model using data from a survey of a large Norwegian energy corporation. Survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 67 publications
3
52
0
Order By: Relevance
“…Howell & Boies, 2004;Howell et al, 2005). Yet, studies in the broader field of leadership showed that men and women use different influence strategies and managerial styles (Foss, Woll, & Moilanen, 2013;Shane, 1995).…”
Section: Champions' Personal Characteristicsmentioning
confidence: 99%
“…Howell & Boies, 2004;Howell et al, 2005). Yet, studies in the broader field of leadership showed that men and women use different influence strategies and managerial styles (Foss, Woll, & Moilanen, 2013;Shane, 1995).…”
Section: Champions' Personal Characteristicsmentioning
confidence: 99%
“…Gender research supports that women need to dedicate time for both work and family. Researchers furnished that organisations are implicitly gendered institutions (Foss, Woll, & Moilanen, 2013). In most of the organisations men are occupied in higher positions (Foss et al, 2013).…”
Section: Agender and Gender Stereotypementioning
confidence: 99%
“…Researchers furnished that organisations are implicitly gendered institutions (Foss, Woll, & Moilanen, 2013). In most of the organisations men are occupied in higher positions (Foss et al, 2013). Ideas generated from women are not implemented in the organizations as compared to men's creative outputs (Lene, Kristin & Mikko, 2013).…”
Section: Agender and Gender Stereotypementioning
confidence: 99%
“…Foss et al ( [5]) provided one explanation for women's inactivity in innovation. Based on their study, women are equally innovative in generating new ideas compared to men, but women's ideas are more seldom implemented in the organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on a wide literature review of gender and innovation, Alsos et al ( [4]) discuss research paths related to 1) gender differences and similarities in innovation, 2) gendered constructions of innovation and 3) gendering processes of innovation. Gender has an effect on how innovations are implemented: women's ideas are not implemented to the same degree as men's ( [5]), and the whole construction of innovation is gendered with masculine connotations ( [6]). Wikhamn and Knights ([7]) show that these masculine discourses are apparent also in open innovations.…”
Section: Introductionmentioning
confidence: 99%